A modeling study of the formation, maintenance, and relaxation of upwelling circulation on the Northeastern South China Sea shelf. (July 2015) - Gan, Jianping; Wang, Jingjing; Liang, Linlin; Li, Li; Guo, Xiaogang
Abstract: We investigated persistent summer upwelling circulation, in response to upwelling and downwelling favorable winds, in the Northeastern South China Sea (NSCS). We used a validated three-dimensional ocean circulation model that was forced by realistic atmospheric fluxes and downscaled coupling of real-time lateral fluxes. We found that upwelling in the NSCS was formed and maintained by the presence of an intensified westward along-isobath pressure gradient force ( PGF m ) and bottom frictional effect that led to cross-isobath currents over the unique NSCS widened shelf. The upwelling favorable PGF m and the frictional effect arose from the interaction between the eastward shelf current and the shelf topography. These intrinsic upwelling dynamics in the NSCS were largely sustained during episodic downwelling winds in the upwelling season because the retreat of the eastward shelf current from pre-existing upwelling was significantly slowed by the unique widened shelf topography. Furthermore, the upwelling dynamics could also be maintained and, even developed, during downwelling favorable winds, when the eastward shelf current was sustained by the pumping of downstream outflow.